2016
DOI: 10.1016/j.ydbio.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Mediator: A key regulator of plant development

Abstract: Mediator is a multiprotein complex that regulates transcription at the level of RNA pol II assembly, as well as through regulation of chromatin architecture, RNA processing and recruitment of epigenetic marks. Though its modular structure is conserved in eukaryotes, its subunit composition has diverged during evolution and varies in response to environmental and tissue-specific inputs, suggesting different functions for each subunit and/or Mediator conformation. In animals, Mediator has been implicated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 124 publications
1
49
0
Order By: Relevance
“…As such, it is somewhat remarkable that, under favorable growth conditions, Arabidopsis is largely robust to perturbation of many Mediator complex subunits. Unlike mice, in which all MED knockouts tested have proved to be embryonic lethal, many of the single Arabidopsis MED mutants studied to date grow well enough in controlled environments that they are fertile (Yin and Wang 2014; Buendía-Monreal and Gillmor 2016). This makes Arabidopsis uniquely suited to studying the effects of disruption of the complex in a developing, multicellular eukaryote.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is somewhat remarkable that, under favorable growth conditions, Arabidopsis is largely robust to perturbation of many Mediator complex subunits. Unlike mice, in which all MED knockouts tested have proved to be embryonic lethal, many of the single Arabidopsis MED mutants studied to date grow well enough in controlled environments that they are fertile (Yin and Wang 2014; Buendía-Monreal and Gillmor 2016). This makes Arabidopsis uniquely suited to studying the effects of disruption of the complex in a developing, multicellular eukaryote.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies showed that MED25 regulates flowering in cooperation with the photoperiod pathway (Iñigo et al ., ; Liu et al ., ). Other than med25 , several mediator subunit mutants also show a late‐flowering phenotype: med8 , med12 , med13 , med15 , med16 , med17 , med18 and med20a (Buendia‐Monreal & Gillmor, ). In addition, three mediator subunits are involved in age‐regulated flowering time; for instance, MED12 and MED13 repress the expression of miR156 , and MED18 interacts with SPL15 to initiate transcription of flowering‐related genes (Gillmor et al ., ; Hyun et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the species, MEDIATOR is a large multimeric protein comprising 25–34 subunits (Allen and Taatjes, ; Samanta and Thakur, ), which are organized in four modules: head, middle, tail and CDK/Cycline (Chadick and Asturias, ; Conaway et al ., ). Each subunit seems to be a specific regulator for defined gene sets related to different functions involved in gene transcription mediated by RNA Polymerase II, including transcription, initiation and elongation, as well as RNA processing, chromatin spatial conformation and enhancer–promoter interaction (Buendía‐Monreal and Gillmor, ).…”
Section: Introductionmentioning
confidence: 99%